Everolimus eluting bioresorbable vascular scaffolds in patients with acute coronary syndromes: Two‐year results from the German‐Austrian ABSORB registry. Issue 4 (17th June 2021) - Tröbs, Monique; Achenbach, Stephan; Nef, Holger M.; Gori, Tomasso; Naber, Christoph; Neumann, Till; Richardt, Gert; Schmermund, Axel; Wöhrle, Jochen; Zahn, Ralf; Hamm, Christian W.; ,
Abstract: Objectives: To identify potential differences in 2‐year outcome between patients who underwent coronary revascularization using bioresorbable vascular scafffolds (BVS) in stable coronary artery disease (CAD) and acute coronary syndromes (ACS). Background: Data from randomized trials suggest a significantly higher event rate following coronary revascularization using everolimus‐eluting BVS as compared to new generation drug eluting stents. Whether particular patient subgroups are at increased risk for scaffold thrombosis and target lesion failure (TLF) has not clearly been demonstrated. Methods: German‐Austrian ABSORB RegIstRy is a prospective all‐comer multi‐center observational study of consecutive patients who were considered for coronary revascularization with BVS. We compared 1499 patients with stable CAD to 1594 patients with ACS. Endpoints were major adverse cardiac events (MACE), TLF, and scaffold thrombosis. Results: While single vessel disease was more prevalent in ACS (46% vs. 37%, p < 0.0001), lesion complexity (B2/C stenosis 37% vs. 36%, bifurcation 2.4% vs. 3.4%, p < 0.05), number of implanted scaffolds/patient (1.34 vs. 1.43), scaffold length (18 vs. 18 mm) or the rate of high pressure postdilatation (68% vs. 70%) did not differ between ACS and stable CAD. Two‐year MACE rates were 11.6% in ACS and 11.4% in stable CAD, TLF occurred in 7.0% versus 7.4% and target vessel revascularization in 8.8 versus 10.2% (n.s. for all). Definite scaffold thrombosis rates were not significantly different (ACS 1.9% vs. stable CAD 2.1%). Conclusion: Real‐world 2‐year event rates after coronary revascularization with BVS are not significantly different between individuals with ACS as compared to stable CAD.